Historical Foundations of Comparative Linguistics: Unraveling the Tapestry of Language Evolution (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This article delves into the historical foundations of comparative  linguistics, tracing its origins from the 18th century to the contemporary era. Beginning  with the groundbreaking insights of Sir William Jones, the narrative explores the birth  of comparative linguistics and its subsequent development through key figures like  Franz Bopp and the Neogrammarians. Emphasizing the Indo-European studies as a  catalyst, the article illuminates the evolution of sound laws and the application of the  comparative method in deciphering linguistic relationships. The article navigates  through challenges and controversies, showcasing the refinement of methods and the impact of technology in the 20th and 21st centuries. Ultimately, it underscores the  enduring significance of comparative linguistics in unraveling the intricate tapestry of  human language evolution.